Cpn60.1 (GroEL1) Contributes to Mycobacterial Crabtree Effect: Implications for Biofilm Formation - Zeng, Sheng; Constant, Patricia; Yang, Dong; Baulard, Alain; Lefèvre, Philippe; Daffé, Mamadou; Wattiez, Ruddy; Fontaine, Véronique (Frontiers in Microbiology, 2019)
Biofilm formation is a survival strategy for microorganisms facing hostile environment. Under biofilm, bacteria are better protected against antibacterial drugs and the immune response, increasing treatment difficulty, as persistent populations recalcitrant to chem-otherapy are promoted. Deciphering mechanisms leading to biofilms could thus be ben-eficial to obtain new antibacterial drug candidates. Here, we show that mycobacterial biofilm formation is linked to excess glycerol adaptation and the concomitant establish-ment of the Crabtree effect. This effect is characterized by respiratory reprogramming, ATP downregulation and secretion of various metabolites including pyruvate, acetate, succinate and glutamate. Interestingly, the Crabtree effect was abnormal in a mycobac-terial strain deficient for Cpn60.1 (GroEL1). Indeed, this mutant strain had a compro-mised ability to downregulate ATP and secreted more pyruvate, acetate, succinate and glutamate in the culture medium. Importantly, the mutant strain had higher intracellular pyruvate and produced more toxic methylglyoxal, suggesting a glycolytic stress leading to growth stasis and consequently biofilm failure. This study demonstrates for the first time the link between mycobacterial biofilm formation and the Crabtree effect.